AN ANALYSIS OF CONTENT AND LISTENING MATERIAL: HOW WELL DOES “ENGLISH FOR NUSANTARA” ALIGN WITH PHASE D LEARNING OUTCOMES? - Yakfi, Choirul; Siswoyo, Siswoyo; Kurniati, Kurniati (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Penelitian ini menganalisis buku teks bahasa Inggris kelas delapan,